Do Existential Variables Mediate Between Religious-Spiritual Facets of Functionality and Psychological Wellbeing - Wnuk, Marcin (Journal of religion and health, 2014)
Religiosity has been related to psychological wellbeing outcomes. Although this relationship is primarily based on studies of church attendance or prayer and wellbeing, more recent work has focused on the potential mechanisms that may mediate the religion-wellbeing findings. One of the major function of religion is finding of meaning of life and improving hope. Recent studies have indicated that hope and meaning of life are the potential variables mediate between religion and wellbeing. It was hypothesized that one pathway through which religiosity may exert its positive influence on psychological wellbeing is through finding meaning of life and improving hope. One study was conducted examining the relationships among spiritual experiences, hope, meaning of life and psychological wellbeing operationalized as satisfaction with life, positive affect and negative affect. The following research tools were used: Daily Spiritual Experiences Scale, Purpose in Life Test, Hearth Hope Index, Cantril Ladder, Positive and Negative Affect Schedule. Meaning of life and hope were noticed to mediate between spiritual experiences and satisfaction with life as well as between spiritual experiences and positive affect. Spiritual experiences were not related to negative affect. Both meaning of life and hope predicted negative affect. This study found meaning of life and hope to be an important factors in the religion-wellbeing relationship and related to positive psychological outcomes, including improved satisfaction with life and positive affect as well as reduced negative affect.